Preparation and Application of Magnetic Responsive Materials in Bone Tissue Engineering - Li, Song; Wei, Changling; Lv, Yonggang (Current Stem Cell Research & Therapy, 2020)
At present, many kinds of materials are used for bone tissue engineering, such as polymer materials, metals, etc., which in general have good biocompatibility and mechanical properties. However, these materials cannot be controlled artificially after implantation, which may result in poor repair performance. The appearance of the magnetic response material enables the scaffolds to have the corresponding ability to the external magnetic field. Within the magnetic field, the magnetic response material can achieve the targeted release of the drug, improve the performance of the scaffold, and further have a positive impact on bone formation. This paper first reviewed the preparation methods of magnetic responsive materials such as magnetic nanoparticles, magnetic polymers, magnetic bioceramic materials and magnetic alloys in recent years, and then introduced its main applications in the field of bone tissue engineering, including promoting osteogenic differentiation, targets release, bioimaging, cell patterning, etc. Finally, the mechanism of magnetic response materials to promote bone regeneration was introduced. The combination of magnetic field treatment methods will bring significant progress to regenerative medicine and help to improve the treatment of bone defects and promote bone tissue repair.
Keywords: magnetic nanoparticle